The quandary of incorrect practice toward unused and expired pharmaceutical products in households - Ali Al-Samydai, Maha N. Abu Hajleh, Mahmood Al-Samydai, Lidia Kamal Al-Halaseh Shahd Habash, Dania Alkhayyat, Sameera Abu Saef, Leen Haitham, Hadeel Sayel Bahloul, Majd Waleed Askender (Journal of Applied Pharmaceutical Science, 2022)
Background: The latest revolution in pharmaceutical industries has led to an enormous production of medications, and therefore massive prescriptions. Sadly, the innocence of the correct disposal methods correlates with the hazardous accumulation of unused and even expired medicines. This is a worldwide issue and needs to be monitored. The current study aims to assess patients and customers’ knowledge, attitude, and awareness of the correct storage conditions of the prescribed medications, in addition to their disposal methods.Methods: Online Google forms were randomly distributed among 450 participants. The achieved response rate was 97%. The questionnaire was titled “Regarding the Factors Influencing Consumers’ Knowledge about Unused and Expired Medications”.Results and conclusion: The output of this study highlights the risk of mishandling expired and unused medications due to people’s knowledge backwardness. The obtained data confirmed the effect of reference groups on patient behavior regarding storage conditions, the disposal of medicines, and the environmental and health hazards related to medications abuse. In essence, establishing a disposal program for unused and expired medicines under the supervision of trained pharmacists is necessary to increase social awareness, therefore alleviating misuse hazards.
Keywords: Unused medication, expired medication, storing conditions, pharmaceutical waste, toxicity